The faunal assemblage from the manufacturing district at Spolverino: from the Roman Imperial period to Late Antiquity - ANICETI, VERONICA; ALBARELLA, UMBERTO; SEBASTIANI, ALESSANDRO (Archaeofauna, 2021)
This paper presents a zooarchaeological analysis from the site of Spolverino (southern Tuscany, Italy). Archaeological excavations have uncovered a complex stratigraphy dated from the Roman Imperial period to Late Antiquity (late 1st- early 6th centuries AD). The industrial function of the site in Imperial times is partially reflected in the nature of the faunal assemblage. In Late Antiquity, Spolverino lost its original manufacturing functions, as many of the workshops were abandoned; our evidence, however, suggests that some livestock was kept, probably managed by a restricted group of people still living in that area. Some hunting was practiced throughout the occupation but it increased in the later periods. Remarkable, in Late Antiquity, is the occurrence of the fallow deer, an introduced species, rare in Roman contexts.